Kewenangan pejabat lelang kelas II terhadap minuta risalah lelang yang lebih batas waktu - Hartina Ruth Manora; Abdul Rachmad Budiono; Endang Sri Kawuryan (University of Merdeka Malang, 2022)
This study aims to determine the position of the minutes of auction minutes after 30 years and the authority of the Auction Officer after the minutes are kept for 30 years. The Minutes of the Minutes of Auction Deed are authentic deeds and have perfect evidentiary power for the parties. In Article 92 paragraphs (3) and (4) of the Regulation of the Minister of Finance (PerMenKeu) Number 27/PMK.06/2016 concerning Auction Implementation Guidelines, it is stated that the minimum period of storage for the Minutes of Auction Deed is 30 years. The position of the minutes of auction minutes that have been kept for 30 years or more, if it is related to the juridical age of the authentic deed, then the position of the minutes of the auction minutes that have been kept for 30 years remains valid as legal evidence. Minutes of Auction made by the Class II Auction Officer are kept at the Class II Auction Officer's Office for 30 years so that the Class II Auction Officer is authorized to make a copy/quote/Grosse after 30 years and is not liable for the minutes of the auction minutes. In terms of enforcing the rights of the parties concerned and requiring the Minutes of Auction that have been kept for 30 years, the parties concerned may take legal action by submitting a request for a court order.How to cite item: Manora, H., Budiono, A., Kawuryan, E. (2022). Kewenangan pejabat lelang kelas II terhadap minuta risalah lelang yang lebih batas waktu. Jurnal Cakrawala Hukum, 13(1), 96-106. DOIhttps://doi.org/10.26905/idjch.v13i1.7096.